Inter- and intra-donor variability in bone marrow-derived mesenchymal stromal cells: implications for clinical applications - Trivedi, Alpa; Lin, Maximillian; Miyazawa, Byron; Nair, Alison; Vivona, Lindsay; Fang, Xiaohui; Bieback, Karen; Schäfer, Richard; Spohn, Gabriele; McKenna, David; Zhuo, Hanjing; Matthay, Michael A.; et al. (Cytotherapy, 2024)
Background aims - Mesenchymal stromal cells (MSCs) are attractive as a therapeutic modality in multiple disease conditions characterized by inflammation and vascular compromise. Logistically they are advantageous because they can be isolated from adult tissue sources, such as bone marrow (BM). The phase 2a START clinical trial determined BM-MSCs to be safe in patients with moderate-to-severe acute respiratory distress syndrome (ARDS). Herein, we examine a subset of the clinical doses of MSCs generated for the phase 2a START trial from three unique donors (1-3), where one of the donors’ donated BM on two separate occasions (donor 3 and 3W). - Methods - The main objective of this study was to correlate properties of the cells from the four lots with plasma biomarkers from treated patients and relevant to ARDS outcomes. To do this we evaluated MSC donor lots for (i) post-thaw viability, (ii) growth kinetics, (iii) metabolism, (iv) surface marker expression, (v) protein expression, (vi) immunomodulatory ability and (vii) their functional effects on regulating endothelial cell permeability. - Results - MSC-specific marker expression and protection of thrombin-challenged endothelial barrier permeability was similar among all four donor lots. Inter and intra-donor variability was observed in all the other in vitro assays. Furthermore, patient plasma ANG-2 and protein C levels at 6 hours post-transfusion were correlated to cell viability in an inter- and intra-donor dependent manner. - Conclusions - These findings highlight the potential of donor dependent (inter-) and collection dependent (intra-) effects in patient biomarker expression.
Online verfügbar: 30. März 2024, Artikelversion: 21. August 2024
Gesehen am 21.10.2024